(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aims to identify the level of clarity of the counseling role among a sample of social counselors in first-cycle schools in the city of Latakia. To achieve the goal of the research, a questionnaire for clarity of the counseling role was constructed and included three dimensions. The research sample consisted of (81) social counselors, the researcher adopted the descriptive approach. The research reached a set of results indicating that clarity of the counseling role was at an average level among social counselors. it was also found that there was no difference between the sample members’ scores on the guidance role clarity questionnaire according to the gender variable. The results indicated that there were differences between the grades of the sample members depending on the academic qualification variable in favor of postgraduate holders. Also, no differences were detected between the grades of the sample members depending no the variable number of the years of service.